Identifying the optimal arm priming exercise intensity to improve maximal leg sprint cycling performance - Matsumoto, T.; Tomita, Y.; Irisawa, K. (Journal of Sports Science & Medicine, 2023)
Priming exercises improve subsequent motor performance; however, their effectiveness may depend on the workload and involved body areas. The present study aimed to estimate the effects of leg and arm priming exercises performed at different intensities on maximal sprint cycling performance. Fourteen competitive male speed-skaters visited a lab eight times, where they underwent a body composition measurement, two VO2max measurements (leg and arm ergometers), and five sprint cycling sessions after different priming exercise conditions. The five priming exercise conditions included 10-minute rest (Control); 10-minute arm ergometer exercise at 20% VO2max (Arm 20%); 10-minute arm ergometer exercise at 70% VO2max (Arm 70%); 1-min maximal arm ergometer exercise at 140% VO2max (Arm 140%); and 10-min leg ergometer exercise at 70% VO2max (Leg 70%). Power outputs of 60-s maximal sprint cycling, blood lactate concentration, heart rate, muscle and skin surface temperature, and rating of perceived exertion were compared between the priming conditions at different measurement points. Our results showed that the Leg 70% was the optimal priming exercise among our experimental conditions. Priming exercise with the Arm 70% also tended to improve subsequent motor performance, while Arm 20% and Arm 140% did not. Mild elevation in blood lactate concentration by arm priming exercise may improve the performance of high-intensity exercise.